Inactivation of Babesia microti in red blood cells and platelet concentrates. Issue 10 (5th September 2017) - Tonnetti, Laura; Laughhunn, Andrew; Thorp, Aaron M.; Vasilyeva, Irina; Dupuis, Kent; Stassinopoulos, Adonis; Stramer, Susan L.
Abstract : BACKGROUND: With an increasing number of recognized transfusion‐transmitted (TT) babesiosis cases, Babesia microti is the most frequently TT parasite in the United States. We evaluated the inactivation of B. microti in red blood cells (RBCs) prepared in Optisol (AS‐5) using amustaline and glutathione (GSH) and in platelet components (PCs) in 100% plasma using amotosalen and low‐energy ultraviolet A (UVA) light. STUDY DESIGN AND METHODS: Individual RBCs and apheresis PCs were spiked with B. microti –infected hamster RBCs (iRBCs) to a final concentration of 10 6 iRBCs/mL and treated with the respective inactivation systems according to the manufacturer's instruction. Samples were collected before (control) and after (test) each treatment. Dilutions of the control samples to 10 −6 were inoculated into hamsters, while the test samples were inoculated neat or at 10 −1 dilution. At 3 and 5 weeks postinoculation, hamsters were evaluated for B. microti infection by microscopic observation of blood smears and 50% infectivity titers (ID50 ) were determined. Log reduction was calculated as control log ID50 minus test log ID50 . RESULTS: Parasitemia was detected in hamsters injected with as low as 100, 000‐fold diluted control samples, while no parasites were detectable in the blood smears of any hamsters receiving neat test samples. Mean log reduction was more than 5 log/mL by amustaline/GSH for RBCs and more than 4.5 log/mL by amotosalen/UVA for PCs. CONCLUSION: B. microti was inactivated to the limit of detection in RBCs and PCs after the respective inactivation treatment. Complete inactivation of B. microti was achieved in this animal infectivity model, and pathogen reduction treatment inhibited transmission of infection.